Evaluation of Oxidative Stress in Ectopic Pregnancies: Oxidative Stress in Ectopic Pregnancies - Üreyen Özdemir, Eda; Yalçın Bahat, Pınar; Topbaş Selçuki, Nura Fitnat; Çakmak, Kübra; Çakmak, Fatih; Neşelioğlu, Salim; Erel, Özcan (Acta Biomedica Atenei Parmensis, 2022)
Purpose: The aim of the study is to show the relationship between oxidative stress and ectopic pregnancy.Materials and Methods: A total of 62 patients, 31 in the ectopic pregnancy group (study group) and 31 in the first-trimester pregnancy (control group) were included in the study. Patients between 18-45 years of age who had tubal ectopic pregnancy diagnosed by transvaginal ultrasonography and serum β-HCG values were included in the study group. Serum thiol- disulfide hemostasis were measured from venous blood.Results: Between the control group and the ectopic pregnant group; there was no statistically significant difference in terms of age, total thiol, albumin, disulfide, index 1 (disulfide / total thiol), index 2 (disulfide / native thiol), and index 3 levels (p> 0.05). The area under the ROC curve for native thiol measurements was statistically significant in distinguishing the control group and the ectopic pregnant group [AUC = 0.657, 95% CI: 0.521-0.793, p = 0.034]Conclusion: This study shows that ectopic pregnancies may be associated with the presence of high oxidative stress. Especially in early stage suspected patients, demonstrating the presence of oxidative stress together with serial β-HCG follow-up may be helpful in diagnosis.